The Influence of Ownership Structure and Company Characteristics on Dividend Policy - Allaudya Roudhotul Firdaus; Ira Maya Hapsari; Mohammad Arridho Nur Amin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the factors determining dividend policy in food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The dividend policy is an important corporate decision because it reflects the management's strategy in balancing shareholder returns and internal financing needs. However, empirical findings regarding the factors influencing dividend policy are still inconsistent, particularly in the manufacturing sector. This study aims to analyze the influence of institutional ownership, asset growth, leverage, and company size on dividend policy, both partially and simultaneously. The population consists of all food and beverage subsector companies listed on the Indonesia Stock Exchange from 2020 to 2024. Using purposive sampling techniques, 19 companies were selected, resulting in 95 company-year observations. The data were analyzed using multiple linear regression analysis. The results show that institutional ownership has a significant influence on dividend policy, while asset growth and leverage do not show a significant influence. The size of the company was found to have a significant positive influence on dividend policy. Simultaneously, institutional ownership, asset growth, leverage, and company size significantly affect dividend policy. These findings suggest that corporate governance through institutional ownership and corporate scale play an important role in determining dividend distribution decisions, while growth opportunities and debt levels are not dominant factors in this subsector. The study contributes to the literature on dividend policy by providing empirical evidence of Indonesia's food and beverage industry and offering practical insights for managers and investors in formulating dividend-related decisions.